Utilização do desempenho nos testes de salto vertical e de corrida de velocidade para monitorar as respostas sub-agudas ao treinamento de sprint repetido - Sylvia Boaventura Diniz Maldonado (2015)
The aim of this study was to determine whether the performances in vertical jump tests and sprint tests can be used to monitor the subacute effects of repeated sprint training. Twelve male subjects underwent 4 repeated sprints training sessions, carried out at intervals between sessions of 72, 48 and 24 hours respectively. The performance achieved during the training sessions were recorded and compared with the performance achieved in the SCM test and sprint test at distances of 10m, 20m, 30m and 40m made at the beginning of each training session. The Friedman ANOVA was used to compare the performance of the group of subjects between training sessions and also to compare the performance of each individual sample between training sessions. When Friedman ANOVA indicated performance gap between sessions, the Wilcoxon test was used to check where those differences were. The Spearman correlation showed that the subject status (fatigue or lack of fatigue) indicated by the SCM test performed at the beginning of each training session had no significant correlation with the state of the subject indicated by the performance recorded during their own training sessions ( r = - 0,180; p> 0.05). The highest correlations between the state of the individual indicated by performance in the sprint test and the status of the individual indicated by performance in their own training sessions took place for the 30m and 40m distances of the sprint test (r = 0.898, p < 0,01 ; r = 0.558, p < 0,01, respectively). It was concluded that the shortest distance of the sprint to monitor individual and subacute responses to repeated sprint training is 30m.